PESAWAT SEDERHANA - Ajeng Sri Rahayu; Dita Amelia (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Judging from their development, uses, and roles in the era of disruption, the material on simple machines (levers, inclined planes, pulleys, and wheels and axles) provides education to students based on the principles of simplicity and non-instant learning. Furthermore, the study of simple machines is relevant to challenges that can be turned into opportunities in the era of disruption, including efforts to upgrade curriculum quality, instill values, awareness of changing times, and self-discovery.